University entrepreneurship education in Tanzania : Teaching context, students’ profiles, expectations and outcomes - Mwasalwiba, E.S. (Vrije Universiteit Amsterdam, 2026)
This study assesses the impact of entrepreneurship education in Tanzanian universities. It explores the teaching methods, student profiles, expectations, and outcomes associated with these programs. Through mixed research methods involving qualitative and quantitative data from multiple institutions, the study finds that while university entrepreneurship education significantly influences students' entrepreneurial intentions, it faces challenges in meeting their expectations. Key factors affecting its effectiveness include misalignment of teaching objectives, limited practical engagement with local business contexts, and the need for better understanding of students' entry profiles. The findings suggest improvements for curriculum design and policy interventions to enhance the impact of entrepreneurship education in Tanzania